The Influence of Accounting Information System Receivables on Internal Control of Receivables (Case Study on One of The Distributors of Cables and Electrical Equipment in West Java) - Annisa Nur Afiyah; Robbi Saepul Rahman; Galih Putra Prawiranegara; Resna Meliawati (P3M, Sekolah Tinggi Ilmu Ekonomi Pasundan Bandung, 2025)
This study seeks to assess the impact of the accounts receivable accounting information system on the internal management of accounts receivable at a cable and electrical equipment distributor in West Java. An excellent accounting information system is crucial in facilitating optimal accounts receivable management. This system ensures the precise and effective recording of accounts receivable transactions, monitors payment due dates, and generates pertinent data for executive decision-making. This study employs a quantitative methodology, utilizing data-gathering approaches by distributing questionnaires to all personnel engaged in accounts receivable management at the organization. The questionnaire was developed by assessing the independent variable of the accounts receivable accounting information system and the dependent variable of internal control over accounts receivable. Data analysis was conducted using various statistical tests, including validity assessments, reliability evaluations, descriptive analysis, and fundamental linear regression analysis. The study's results demonstrate a robust and significant correlation between the accounts receivable accounting information system and the internal control of accounts receivable. Establishing an effective accounting information system can enhance internal control efficacy by ensuring transaction recording accuracy, facilitating real-time accounts receivable monitoring, and regulating the company's credit policy. This system mitigates the risk of bad debts by delivering prompt and precise information to management, enabling appropriate preventive measures. Nonetheless, several elements beyond the accounts receivable accounting information system influence the internal control of accounts receivable, including management policies, personnel competencies, and the technology infrastructure that facilitates system implementation. Consequently, organizations are encouraged to enhance the deployment of accounts receivable accounting information systems by offering ongoing employee training, performing regular assessments of system efficacy, and creating more advanced system functionalities. Furthermore, organizations must enhance accounts receivable management rules and improve interdepartmental collaboration to achieve superior internal control. This study concludes that the accounts receivable accounting information system significantly enhances internal control over accounts receivable. Establishing an effective system enhances operational efficiency while also augmenting transparency and accountability in accounts receivable management. This study's implications offer firms insight into the significance of employing information technology in internal control, particularly in mitigating the risk of losses from bad debts. This study aims to serve as a foundation for firms to sustainably enhance the quality of accounting information systems and internal controls.